2021
DOI: 10.1186/s12868-021-00677-6
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytic lesions of the bilateral ventrolateral orbital cortex not only directly reduce depression-like behavior but also decreased desperate behavior induced by chronic unpredicted mild stress in rats

Abstract: Background Previous studies have revealed that ventrolateral orbital cortex (VLO) may play an important role in the regulation of emotional behavior. However, it is not known what effect VLO damage will have on emotion regulation. Results Data showed that damage of VLO increased the anxiety-like behavior in open field test and elevated plus maze, and decreased the depressive behavior in forced swimming test and learned helplessness test. Besides, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…While the downstream targets of the activation of 5-HT 2A R is not fully illustrated, studies have shown that psilocybin and other psychedelics induced long-term plasticity change and gene expression change in neurons 58 , suggesting increased excitatory transmission in the brain. On the other hand, studies also showed that lesion or chronic inactivation of the OFC decreased depression-like behavior in rats 59, 60 .…”
Section: Discussionmentioning
confidence: 99%
“…While the downstream targets of the activation of 5-HT 2A R is not fully illustrated, studies have shown that psilocybin and other psychedelics induced long-term plasticity change and gene expression change in neurons 58 , suggesting increased excitatory transmission in the brain. On the other hand, studies also showed that lesion or chronic inactivation of the OFC decreased depression-like behavior in rats 59, 60 .…”
Section: Discussionmentioning
confidence: 99%